COLLABORATIVE GOVERNANCE MITIGASI BENCANA BANJIR DI INDONESIA: SYSTEMATIC LITERATURE REVIEW (SLR) DARI TAHUN 2018-2023 - Alvina Hapsari, Amanda Alvina Hapsari; Zarkasyi Rahman, Amni (Journal of Public Policy and Management Review, 2025)
Much research has been carried out regarding collaborative governance in flood disaster mitigation. However, there has been no research regarding the structure of knowledge development on the topic of collaborative governance, flood disaster mitigation. Therefore, it is necessary to understand collaborative governance for flood disaster mitigation through a systematic literature review process as an effort to find novelty. The systematic literature review process was carried out using PRISMA guidelines. The literature search site used is Google Scholar. The inclusion criteria for the selected articles are: 1) Published in English and Indonesian, 2) Published from 2018-2023, 3) Availability of literature using articles with full text, 4) Publication stage in the form of final press and 5) Document type in the form of a journal . The development of publications in the field of collaborative governance in flood disaster management in Indonesia shows an increase in numbers from year to year, with the most publications in the period 2018 to 2023, namely in 2023 with the prominent keyword "disaster" which has a connection between keywords and keywords. others are "mitigation" and "flash flood". The analysis carried out by researchers revealed that there are six aspects that are dimensions in collaborative governance for flood disaster mitigation, including: Network structure, Commitment to shared goals, Trust between participants, Access to authority, Sharing information, Access to resources. The aspect that is much discussed is commitment to goals, while the aspect that is less discussed is access to power. Therefore, researchers suggest that aspects that have not been widely discussed, namely access to power, be studied more in future research.